Penile lesion in end-stage renal failure — cancer or otherwise?: Calcific uremic arteriolopathy presenting with a penile lesion - Malthouse, Theo; Lam, Wayne; Brewin, James; Watkin, Nick; Ayres, Benjamin; Nitkunan, Tharani (Canadian Urological Association Journal, 2015)
Calcific uremic arteriolopathy or calciphylaxis is a rare condition that can present with clinical features similar to penile cancer. It is a diagnosis to consider in patients with end-stage renal failure (ESRF) presenting with a penile lesion. We describe one such case, where a patient with ESRF presented with a solid, tender penile mass and underwent surgery for presumed penile cancer. Histopathological analysis however confirmed a diagnosis of calcific uremic arteriolopathy, without evidence of malignancy. The clinical diagnosis of calcific uremic arteriolopathy relies on a high index of suspicion, and lesion biopsy is controversial due to a high risk of poor wound healing and sepsis. New treatment options are encouraging, and have been reported, albeit in small numbers. Delayed diagnosis can adversely affect both quality of life and prognosis in a condition with an extremely high mortality rate.